An additively manufactured titanium tilting suture anchor: a biomechanical assessment on human and ovine bone specimens - Abedi, Ali; Pourghazi, Farzad; Eslami, Maysa; Nabian, Mohammad Hossein; Ali Mohammadi, Ali Mohammad; Zanjani, Leila Oryadi; Farahmand, Farzam (Frontiers in Surgery, 2023)
A novel titanium tilting suture anchor was designed and fabricated using additive manufacturing. The anchor enjoyed a nonsymmetrical structure to facilitate its insertion through a weight-induced tilt, a saw-teeth penetrating edge to provide a strong initial fixation into cancellous bones of various densities, and an appropriate surface texture to enhance the long-term fixation strength through bone ingrowth. Biomechanical tests were performed on 10 ovine and 10 human cadaveric humeri to examine the insertion procedure and assess the initial fixation strength of the anchor in comparison with a standard screw-type anchor as control. Results indicated a simple yet reliable insertion procedure for the tilting anchor. All anchors survived after 400 cycles of cyclic loadings and failed in the load-to-failure step. There were no significant differences between the displacements and fixation stiffnesses of the anchors in either group. Also, there were no significant differences in ultimate failure loads in the ovine group (273.7±129.72 N vs. 375.6±106.36 N) and the human group (311.8±82.55 N vs. 281.9±88.35). Also, a larger number of tilting anchors were pulled out in ovine group (6 vs. 3) but a smaller number in the human group (4 vs. 6). It was concluded that the biomechanical performance of the designed tilting anchor is comparable with that of the standard screw-type anchors.